2017
DOI: 10.1111/add.13968
|View full text |Cite
|
Sign up to set email alerts
|

Measuring treatment outcomes in gambling disorders: a systematic review

Abstract: Background and AimsConsiderable variation of outcome variables used to measure recovery in the gambling treatment literature has precluded effective cross‐study evaluations and hindered the development of best‐practice treatment methodologies. The aim of this systematic review was to describe current diffuse concepts of recovery in the gambling field by mapping the range of outcomes and measurement strategies used to evaluate treatments, and to identify more commonly accepted indices of recovery.MethodsA syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 92 publications
3
69
0
1
Order By: Relevance
“…Por ejemplo, Weinstock et al (2011) concluyeron que los factores sociodemográficos, la severidad del juego, el endeudamiento, y el nivel de coerción ejercido por parte de las redes legales y sociales son predictores de la aceptación o rechazo al tratamiento. Los patrones de juego (Pickering, Keen, Entwistle y Blaszczynski, 2018), las comorbilidades (Maniaci et al, 2017), y el apoyo interpersonal también han surgido como índices valiosos del curso del tratamiento y de sus resultados.…”
Section: Impulsividad Y Curso Del Tratamiento Del Trastorno Por Juegounclassified
“…Por ejemplo, Weinstock et al (2011) concluyeron que los factores sociodemográficos, la severidad del juego, el endeudamiento, y el nivel de coerción ejercido por parte de las redes legales y sociales son predictores de la aceptación o rechazo al tratamiento. Los patrones de juego (Pickering, Keen, Entwistle y Blaszczynski, 2018), las comorbilidades (Maniaci et al, 2017), y el apoyo interpersonal también han surgido como índices valiosos del curso del tratamiento y de sus resultados.…”
Section: Impulsividad Y Curso Del Tratamiento Del Trastorno Por Juegounclassified
“…In a systematic review, Pickering et al . concluded that treatment outcomes for gambling disorder remain defined poorly and assessed inconsistently. Few studies captured variables identified within the Walker et al .…”
Section: Declaration Of Interestsmentioning
confidence: 99%
“…In studies that Pickering et al . reviewed, assessment of non‐gambling constructs was in many ways better than assessment of gambling‐related constructs. Indices administered to evaluate psychological distress and symptoms, for example, are used widely and have substantial evidence of reliability and validity.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 2 more Smart Citations